PENGALAMAN MAHASISWA YANG MENGALAMI INSOMNIA SELAMA MENGERJAKAN TUGAS AKHIR - Noerma Shovie Rizqiea; Elis Hartati (Jurnal Keperawatan Diponegoro, 2012)
The interview that was done by the researcher to 25 informants of students gave a preliminary data, 10 of students stated that they have insomnia while doing their final project. The general purpose of this study was to identify student experiences of class 2008 PSIK FK UNDIP in doing their final project. This research was qualitative study with phenomenological approach. The method of collecting data was in-depth interview with 5 informants from student of class 2008 PSIK FK UNDIP who experience insomnia during their final project. Technic data analyze in this research used data analyzed by Miles and Huberman. The result of this research was identified several themes : definition of insomnia (insomnia sleep duration, a period of insomnia, sleep quality of insomnia, and classification of insomnia); cause of insomnia (internal factors and external factors); time occurrence of insomnia (initial insomnia, frequent of waking, sleep preparation, and late insomnia), the negative impact of insomnia (decreased activity, health problems, and mood decline), the positive impact of insomnia (the achievement of desired target); action taken when there was insomnia (make a sleep schedule, create a comfortable environment, doing an activity before sleep, and nutritional management before going to bed); prevention of insomnia (make a sleep schedule, getting used to sleep on time, and custom made​​). Nurses are expected to provide nursing intervention students who experience insomnia